ANALYTICAL AND NUMERICAL STUDY OF COMPOSITE FLAT ROOFS CONTAINING PLASTERBOARD AND AÇAÍ PIT RESIDUE - Nascimento, Ubiraci Silva; Tavares, Marcio da Silva; Moreira, Edvan; de Oliveira, Fernando Lima; Pestana Filho, José de Ribamar; Beckman, Valter Valder Reis; de Oliveira, Lucas Santos; da Silva, Izak Oliveira Sousa; Batista, Isabelle Cristina dos Reis de Andrade; Lima, João Pedro Silva; Coelho, Gleuberth Ruan Pontes; Dias, Pedro Victor Braga (Editora Impacto Científico, 2025)
In this project, we used concepts of thermal conductivity and heat transfer applied to flat ceilings, exploring the fact that thermal conductivity varies from material to material, thus providing an opening in the range of studies in the area of mathematical and numerical analysis of this variation. To this end, a MATLAB code was used, applying the explicit MDF - finite difference method in the explicit model, starting from the discretization of the thermal diffusion equation, where the simulations were performed based on data obtained from the thermophysical properties of materials found in the literature, as well as data obtained experimentally, where the thermal conductivities and specific mass of gypsum boards with different additions of açaí pulp biomass were used. The analyses focused on evaluating the effects of varying the percentage of biomass added to the gypsum boards and the thickness of the ceiling, as well as analyzing and comparing the efficiency of flat ceilings made with different types of materials. We intend for the results of this study to contribute to another construction alternative, with an emphasis on the thermal aspect of environments. DOI: https://doi.org/10.56238/edimpacto2025.089-005